Analisis Kerusakan Melalui Predictive Maintenance pada Main Drive Raw Mill Indarung II/III - Lukman Alrasyid; Jhon Malta (METAL: Jurnal Sistem Mekanik dan Termal, 2020)
A main drive is an important mobilizing motor component in a raw mill. Due to the extremely condition of constant operation of the raw mill results in failure of the main drive. This disturbs the raw mix intake and halts the next processes. In order to observe and diagnose the cause of failure on the main drive, it is important to conduct a maintenance. The Predictive maintenance technique utilized in this research is the vibration analysis technique.The measuring process of the vibration is conducted through the use of transducer velocity in radial and axial directions on the drive and non-drive components of the RIM03 motor and the symetro gear. The vibration, spectrum, velocity, and speed of rotation are analyzed in the x-Viber. Based on the vibration measurement data, the root cause of vibration can be analyzed through spectrum velocity. In this research, the critical result is found at the LS symetro gear. The occurred problem on the LS symetro gear is caused by misalignment shaft on the symetro gear connecting to gear pinion. The solution which can be applied is heat treatment to the shaft, therefore misalignment can be reduced.